The natives, naturalized and adventives Umbelliferae of La Pampa, Argentine (Semiárida, 2020)
In this contribution the whole genera and species of the Umbelliferse Juss. family which grows spontaneously in the Province of La Pampa, Argentine, are listed. This family is represented by 21 genera with 30 species. Keys for the identification of the genera and species are Included. A short description, distribution, origin and diffusion in La Pampa of each specie is attached.
Keywords: Umbelliferae; La Pampa; Argentine; genera and species